The incidence, hospitalisations and deaths in acutely ill children with dysnatraemias. (8th April 2022) - Lehtiranta, Saara; Honkila, Minna; Anttila, Silja; Huhtamäki, Heikki; Pokka, Tytti; Tapiainen, Terhi
Abstract: Aim: The aim was to evaluate the incidence, hospitalisations and deaths in acutely ill children with dysnatraemias. Methods: This was a register‐based cohort study of 46 518 acutely ill children aged <16 years who visited a paediatric emergency department. Risk factors were assessed using two nested case–control studies. Results: Moderate to severe hypernatraemia occurred in 92 children (0.20%; 95% confidence interval [CI]: 0.16%–0.24%) and moderate to severe hyponatraemia in 131 children (0.28%; 95% CI: 0.24%–0.33%). Underlying medical conditions increased the risk of both moderate to severe hypernatraemia (odds ratio [OR]: 17; 95% 5.5–51) and moderate to severe hyponatraemia (OR: 3.5; 95% CI: 2.0–5.9). The use of a feeding tube (OR: 14; 95% CI: 3.2–66) and intellectual disability (OR: 7.3; 95% CI: 3.0–18) was associated with moderate to severe hypernatraemia. The risk of death was associated with moderate to severe hypernatraemia (OR: 19; 95% CI: 2.0–2564) and moderate to severe hyponatraemia (OR: 33; 95% CI: 3.7–4311). Conclusions: Severe dysnatraemias were more prevalent in acutely ill children with underlying medical conditions and were markedly associated with the risk for death.